Cutinase: Preparation and Application - Jing Wu; Zheng Fei Yan (Cutinase: Preparation and Application, 2021)
The book summarizes the preparation and application of baterial cutinase, which offers the author a chance to comprehensive understanding of cutinase and lays the foundations for application of cutinase in the future. Firstly, his book provides the systemic information of Thermobifida fusca cutinase, such as concept, source, identification, phylogenetic evolution, and crystal structure. Secondly, its functional activity of cutinase was investigated and increased by molecular modification. Thirdly, the large-scale preparation of cutinase was introduced by overexpression and fermentation strategy. Lastly, the book enumerates some cases about application of cutinase as natural green friendly methodology in textile, papermaking and ester synthesis industry. The book is written for researchers, professional/practioners and graduate students in the field of cell biology, molecular biology and biophysics.